Customizing insulation material properties for building retrofitting : from infrared thermography to additive manufacturing - Craveiro, Flavio (2018)
The European Commission proposed a recast to the Energy Efficiency Directive with a target of 30% energy efficiency for 2030. Buildings are the largest energy consumers sector in EU. To reduce the energy consumption of existing buildings and promote energy efficiency retrofit, it is important to improve the thermal performance of the building envelope, acting on thermal bridges to enhance the optimal thermal comfort for building occupants.